Odpowiedzi

  • Użytkownik Zadane
2010-03-11T19:13:39+01:00
A) (-3¼)² + (-2) * (-4)
10 ⁹/₁₆+8=18⁹/₁₆

b) (-3½) * 5 - (-3)³
-17½-9=-26½

c) 2¼ * (-1¹/₉) + 4²
-2½+16=13½

d) (-2½ + 3)² - (-4 + 3½)²
6¼-15+9-16+28+12¼=24,5
2010-03-11T19:15:42+01:00
A) (-3¼)² + (-2) * (-4)=10 ⁹/₁₆+8=18⁹/₁₆
b) (-3½) * 5 - (-3)³=-17½-9=-26½
c) 2¼ * (-1 i jedna dziewiąta) + 4²=-2½+16=13½
d) (-2½ + 3)² - (-4 + 3½)²=6¼-15+9-16+28+12¼=24,5
Najlepsza Odpowiedź!
2010-03-11T19:31:18+01:00
A) (-3¼)² + (-2) * (-4)=10 ⁹/₁₆+8=18⁹/₁₆
b) (-3½) * 5 - (-3)³=-17½-9=-26½
c) 2¼ * (-1 i jedna dziewiąta) + 4²=-2½+16=13½
d) (-2½ + 3)² - (-4 + 3½)²=6¼-15+9-16+28+12¼=24,5